Emotion Dysregulation Predicts Dropout from Prolonged Exposure Treatment among Female Veterans with Military Sexual Trauma-Related Posttraumatic Stress Disorder - Gilmore, Amanda K. (Womens Health Issues, 2020)
BACKGROUND: Military sexual trauma (MST) is notably prevalent among military personnel and can result in mental and physical health problems, including posttraumatic stress disorder (PTSD). Although there are several evidence-based treatments for MST-related PTSD, including Prolonged Exposure therapy (PE), it is unclear what factors are associated with premature termination (i.e., dropout) from this treatment. Given the popularity of PE as an evidence-based treatment for PTSD, the examination of variables that influence dropout from PE among women veterans with MST is warranted. Identification of these specific factors may assist clinicians in addressing the unique symptom profiles and potential barriers to treatment access for individual MST survivors. METHODS: The current study presents secondary data analyses from an ongoing randomized clinical trial that compared the effectiveness of PE delivered in person to delivery via telemedicine for women veterans with MST-related PTSD (n = 136). RESULTS: A total of 50% of participants dropped out from the study (n = 68). Difficulties with emotion regulation at baseline were associated with treatment dropout (odds ratio = 1.03, p < .01), while baseline PTSD and demographic factors were not. CONCLUSIONS: Findings from the current study indicate that emotion regulation skills deficits contribute to PE dropout and may be an appropriate target to address in future clinical trials for PTSD.